Crane Principle Revisited - Kadry, Hamed M. (Plast Reconstr Surg Glob Open, 2020)
BACKGROUND: Scalp and forehead defects represent one of the most complex defects for reconstruction. The nature of these sites being hair bearing, together with the complicated nature of the injuries, for example, electrical burns and motor vehicle accidents, and of course the aesthetic concern being in the face, all add to the complexity of reconstruction. METHODS: This is a case series representing the experience of the authors in using the “crane principle” in the reconstruction of various defects in the forehead and the scalp presented to emergency department, Cairo University Hospital, for the period between January 2018 and January 2019. RESULTS: Twenty patients, 15 men and 5 women, presented with various soft tissue defects of the forehead and the scalp. The injuries of eighteen patients were due to motor vehicle accidents, and 2 patients had postelectrical burns. Age range was from 20 to 65 years, with a mean follow-up of 8 months. The number of total complications was 5. Three patients had wound dehiscence, and 2 patients had ulceration in the grafts placed at the flap donor site. CONCLUSION: Crane principle represents an adequate reconstruction tool for forehead and scalp defects especially when the access to free flap and more complex reconstruction techniques is not available.